Peningkatan Komunikasi Dan Hasil Belajar Pada Pembelajaran Matematika Melalui Media Sederhana(PTK Bagi Siswa Kelas VII Semester Genap SMP Negeri 2 Teras TahunAjaran 2014/2015) - KARNIAWATI, DANIS (2016)
The purpose of this study is to improve communication and learning outcomes of students of class VII E SMP N 2 Teras through simple media. This study includes classroom action research. Class VII E totaling 35 students as recipients subject and the teacher acts as the subject of the action giver. Data collection method used when research is observation, interviews, field notes, test and documentation. Data analysis techniques used by researchers is data reduction, data presentation and conclusion. The results showed an increase in communication improvement can be seen from 1) students express mathematical ideas by talking, 11.43% of the initial conditions increased to 77.14%, 2) students write mathematical ideas, 17.14% of the initial conditions increased to 71, 43%, 3) students in expressing ideas, from the initial conditions increased 8.57% to 74.29%, 4) students to explain, listen, inquire and cooperation, from the initial conditions of 5.71% increased to 80%. An increase in students' mathematics learning outcomes can be seen from the minimum completeness criteria ≥ 75, of the first condition 14.29% increase to 85.71%. Keywords: learning outcomes, communicate, simple media.